Determinants of Medication Compliance among Pulmonary Tuberculosis Patients in the North Cimahi Community Health Center Work Area - Yunita Sarah Nadeak; Eva Elfrida Pardede; Tiarmaida Sitio (International Journal Of Health Science, 2025)
In Indonesia, tuberculosis (TB) remains a global public health problem. The results of an initial survey in the North Cimahi Community Health Center work area The data obtained shows that the number of patients with pulmonary tuberculosis with positive smear is 106 patients. The purpose of this study is to analyze the determinants of adherence to taking medication in pulmonary tuberculosis patients in the area. This study uses a cross-sectional design . The population taken is all pulmonary tuberculosis patients in the working area of the North Cimahi Health Center as many as 106 people, with a total sample of 51 people. Data analysis uses the chi-square test and linear logistic regression. The results of the study showed that there was a relationship between knowledge (0.000), attitude (0.000), education (0.000), work (0.001), and family support (0.000) on medication adherence. Knowledge was the dominant factor influencing medication adherence in pulmonary TB patients with an OR value (Exp B = 29.169 ).It is hoped that health workers will always remind TB sufferers when taking medication to pay more attention to the regularity of taking medication , while TB sufferers are expected to be regular in taking medication and take medication according to the schedule .